Collaboration to Build Resilient Farmers' Human Resources: Digital Literacy Program in Agriculture as a Joint Education Effort - Syafuddin, Khairul; Meidina, Aulia Putri (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2023)
This article aims to examine the importance of the role of government and society in collaborating, especially in improving society's capabilities in the agricultural sector. In this case, development communication has an important role, especially in the form of participatory development communication and community empowerment. However, technological aspects cannot be separated from development communication. Electronic agriculture (e-Agriculture) has become something that farmers need to do to improve the quality of their agriculture. Since the penetration of information and communication technology, the use of this technology has become increasingly massive, especially in searching for information. This encourages the active role of government and society in providing facilities to support the development of human resources for farmers. In this case, digital literacy skills are very important for farmers to have, starting from searching for information, managing information resources, forming digital collaborations, to efforts to increase digital participation. These skills need to be built wisely so that the use of technology in the agricultural realm can be carried out well.